2014
DOI: 10.1063/1.4892882
|View full text |Cite
|
Sign up to set email alerts
|

Experimental indication for band gap widening of chalcopyrite solar cell absorbers after potassium fluoride treatment

Abstract: The implementation of potassium fluoride treatments as a doping and surface modification procedure in chalcopyrite absorber preparation has recently gained much interest since it led to new record efficiencies for this kind of solar cells. In the present work, Cu(In,Ga)Se2 absorbers have been evaporated on alkali containing Mo/soda-lime glass substrates. We report on compositional and electronic changes of the Cu(In,Ga)Se2 absorber surface as a result of a post deposition treatment with KF (KF PDT). In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
108
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 22 publications
10
108
1
Order By: Relevance
“…A surface bandgap widening was observed after a KF PDT also experimentally. [8,9] These results hint to the fact that similar to a KF PDT, a RbF PDT introduces a surface layer, which might be responsible for the blocking of the diode current. That Rb-containing surface layer is subsequently called RIS layer.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A surface bandgap widening was observed after a KF PDT also experimentally. [8,9] These results hint to the fact that similar to a KF PDT, a RbF PDT introduces a surface layer, which might be responsible for the blocking of the diode current. That Rb-containing surface layer is subsequently called RIS layer.…”
Section: Discussionmentioning
confidence: 87%
“…[25] It was found that similar to a KF PDT, a surface layer forms. [5][6][7][8][9]26,30] Additionally, as presented here for a RbF PDT, with the introduction of a KF PDT, a blocking of the diode current was observed. [15] Recently, Malitckaya et al calculated the bandgap energies of AlkInSe 2 (Alk = Li, Na, K, Rb, Cs) secondary phases, which are expected to segregate on the surface of the CIGS absorber for K, Rb, and Cs.…”
Section: Discussionmentioning
confidence: 89%
“…[2]- [5] A controlled incorporation of alkali elements in the absorber by means of a post-deposition treatment (PDT) employing alkali-fluorides helps to further enhance performance. [6]- [8] While it was shown that a combined NaF/KF-PDT significantly enhances the device efficiency [7], its impact on the chemical, electronic, and topographical absorber structure is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The Cu-depleted layer was found to have a wider surface band gap than untreated absorbers [16,19] [24e26]). Whether the ion exchange reaction is limited to the grain boundaries or appears also in the bulk is not known currently.…”
Section: Alkali Treatmentmentioning
confidence: 99%
“…(i) The potassium treatment creates a completely Cudepleted surface layer, which can be continuous [3,16] or structured [15], depending on the exact treatment conditions. The Cu-depleted layer was found to have a wider surface band gap than untreated absorbers [16,19] [24e26]).…”
Section: Alkali Treatmentmentioning
confidence: 99%